A Double-Bridge Channel Shape of a Membraneless Microfluidic Fuel Cell - Ji-Hyun Oh; Muhammad Tanveer; Kwang-Yong Kim (Energies, 2021)
A double-bridge shape is proposed as a novel flow channel cross-sectional shape of a membraneless microfluidic fuel cell, and its electrochemical performance was analyzed with a numerical model. A membraneless microfluidic fuel cell (MMFC) is a micro/nano-scale fuel cell with better economic and commercial viability with the elimination of the polymer electrolyte membrane. The numerical model involves the Navier–Stokes, Butler–Volmer, and mass transport equations. The results from the numerical model were validated with the experimental results for a single-bridge channel. The proposed MMFC with double-bridge flow channel shape performed better in comparison to the single-bridge channel shape. A parametric study for the double-bridge channel was performed using three sub-channel widths with the fixed total channel width and the bridge height. The performance of the MMFC varied most significantly with the variation in the width of the inner channel among the sub-channel widths, and the power density increased with this channel width because of the reduced width of the mixing layer in the inner channel. The bridge height significantly affected the performance, and at a bridge height at 90% of the channel height, a higher peak power density of 171%was achieved compared to the reference channel.